Dependence of the critical temperature on microscopic parameters in the three-dimensional Ising-like systems - Kozlovskii, M.P.; Dukhovii, V.V.; Pylyuk, I.V. (Condensed Matter Physics, 2000)
The critical behaviour of the three-dimensional Ising-like system on a simple cubic lattice with an exponentially decreasing interaction potential is investigated within the collective variables method. The solution of the equation for the phase transition temperature is obtained by taking into account the dependence of its coefﬁcients on the temperature. The dependence of the critical temperature on the interaction potential range is studied.